An update on the ornamental fish industry in Malaysia: Aeromonas hydrophila-associated disease and its treatment control - Anjur, Norashikin; Sabran, Siti Fatimah; Mohd Daud, Hassan; Othman, Nor Zalina (Veterinary World, 2021)
the second position after Singapore. Because of their artistic appeal and tremendous commercial value for international trade, ornamental fish recently gain rapid importance for foreign exchange and as a source of employment. While ornamental fish production is growing, there is an increase in infectious diseases, resulting in high fish mortality with significant economic loss. Bacterial disease is a serious problem for ornamental fish industry. Bacterial species surveillance in diseased freshwater ornamental fish from an aquarium shop reveals that Aeromonas hydrophila is the most dominant bacteria isolated. Consequently, Malaysia is stepping up its efforts by implementing the Economic Transformation Program and other biosecurity steps to address the aquaculture issues and encourage the regrowth of the ornamental fish market. Chemotherapeutic medications, phytobiotics, probiotics, yeast extracts, vaccines, and disinfectants can be used in controlling bacteria. Further studies should be done to find new antibacterial agents from natural sources to combat bacterial fish diseases and reduce fish mortality rate in sustainable aquaculture farms. This review summarizes the literature on ornamental fish industries and aquaculture production in relation to A. hydrophila-associated diseases and ornamental fish health management in Malaysia.